Konstruksi Identitas Masyarakat Dayak Melalui Budaya Baroah Dalam Membangun Citra Desa Sompak di Kabupaten Landak - Sonia Glory Desinta; Rini Darmastuti (Avant Garde, 2019)
One of the assets of culture in Indonesia is Baroah culture from Dayak Kanayatn, which located in Sompak village. Thanksgiving and respect to the god are the expressions from the Baroah culture, which is done from generation to generation. The expression of each culture, constructs the identity of a society that influences other people's perceptions of the community and the area where they are, and has an impact on the image of the region. Based on this perspective, the purpose of this paper is constructs the identity of Sompak village people from Baroah culture, as a strategy to build the image of the Landak district.This paper is based on the results of research conducted using qualitative methods and ethnographic approaches, as well as in-depth interviews and observations to the head of the Sompak sub-district customary council, the head of the Sompak village traditional council and the head of the Sompak village farmers. The result of this paper are : a). Baroah culture is a thanksgiving to Jubata for the rice harvest, health and avoiding disaster and in it there is a Nyangahatn ritual that contains prayers and teaches us to respect customs, traditions and especially Jubata, because everything that humans have comes from God, b). Identity The people of Sompak Village made an image as a society that holds into tradition.